Physiotherapists working in clinics have increased risk for new-onset spine disorders: a 12-year population-based study. Issue 32 (August 2016) - Liao, Jen-Chieh; Ho, Chung-Han; Chiu, Haw-Yen; Wang, Yu-Lin; Kuo, Li-Chieh; Liu, Cheng; Wang, Jhi-Joung; Lim, Sher-Wei; Kuo, Jinn-Rung
Abstract : Abstract: Health care professionals are known to have a high risk for work-related musculoskeletal disorders. However, the information on the risk of new-onset spine-related musculoskeletal disorders (SRMDs) in health care professionals is insufficient. This study aimed to investigate new-onset spine disorder associations among physical, occupational, and pharmacy health care professionals working in different workplaces. Taiwan's National Health Insurance Research Database for registered medical personnel claims from 2000 to 2011 was analyzed. An age- and sex-matched longitudinal cohort study of 7448 subjects (1682 physiotherapists, 1682 occupational therapists [OTs], and 3724 pharmacists) with or without new-onset spine disorders was conducted. The hazard ratios for the development of new-onset spine disorders were estimated among these 3 groups. The overall percentage of new-onset SRMD for physiotherapists is 32.12. The median time from obtaining a registered license to developing SRMD is 1.94 years. The log-rank test showed that physiotherapists have the least possibility of having a SRMD-free rate ( P < 0.0001). The Cox model showed that physiotherapists have a higher risk of new-onset SRMD (hazard ratio: 1.65, 95% confidence interval: 1.48–1.84, P < 0.0001) compared with OTs and pharmacists. Physiotherapists working in clinics have a 2.40-fold increased risk of developing SRMD (95% confidence interval: 1.97–2.92, P < 0.0001) relative to OTs and pharmacists. This may be the first study regarding new-onset SRMD in physiotherapists based on a powerful nationwide population-based database. We conclude that working in clinics is a potential risk for new-onset SRMD in physiotherapists. Therefore, we suggest that physiotherapists should pay more attention to this issue to prevent the development of spine disorders.